Laparoscopic distal gastrectomy and Roux-en-Y reconstruction - Inaki, Noriyuki (Annals of Laparoscopic and Endoscopic Surgery; Vol 2 (March 2017): Annals of Laparoscopic and Endoscopic Surgery, 2017)
In recent years, laparoscopic distal gastrectomy has become common, and gastrectomy has gained consensus as a suitable treatment for early stage stomach cancer. The efficacy of laparoscopic gastrectomy for advanced cancer and total laparoscopic gastrectomy and proximal gastrectomy for upper gastric cancer is currently being studied. This paper will illustrate and provide a summary of our laparoscopic distal gastrectomy with D1+ dissection performed for early stage gastric cancer that will be helpful when the procedure is introduced in various facilities. This paper will also present the Roux-en-Y reconstruction method. Laparoscopic distal gastrectomy with D1+ dissection is generally prescribed for clinical stage IA cancer that was diagnosed prior to surgery. Technical tips, tricks and pitfalls: when performing a dissection, close attention should be paid to keeping the visual field expansion and operative field dry. In addition to standardizing expansion, the electronic devices normally used to perform surgery are laparoscopic coagulating shears, Bipolar Maryland dissectors, and suction and water delivery devices with a button electrode. With regard to reconstruction, the Y limb can usually be created from the small laparotomy surface in the navel. Depending on the capabilities of the surgeon, the abilities of the team, and the level of familiarity, when it is possible to do from the small laparotomy, it is recommended to be performed under direct visual guidance.